Indirect herbivore biomanipulation may halt regime shift from clear to turbid after macrophyte restoration. (15th November 2022) - Zhang, Chengxiang; Pei, Hongcui; Lu, Cai; Liu, Cunqi; Wang, Wei; Zhang, Xiaobo; Liu, Peizhong; Lei, Guangchun
Abstract: Eutrophication transforms clear water into turbid water in shallow lakes. Current restoration techniques focus on re-establishing the clear-water state rather than on its maintenance. We investigated the response of submerged macrophytes to temporary grass carp ( Ctenopharyngodon idella ) and scraping snail ( Bellamya aeruginosa ) introductions. We also explored the impacts of herbivores on underwater light conditions to identify their long- and short-term potential to halt regime shift from clear to turbid after clear-water state reestablishment. Herbivores reduced both the biomass of submerged macrophytes and accumulated nutrients in the tissue of submerged macrophytes. This potentially avoided the pulse of endogenous nutrient release which would have exceeded the threshold required for the regime shift from clear to turbid. However, herbivores had a non-significant impact on submerged macrophyte-reduced light attenuation coefficient, which has a positive linear relationship with water chlorophyll a . Further, grass carp and snails enhanced the inhibition ratio of submerged macrophytes to phytoplankton by 3.96 and 2.13 times, respectively. Our study provides novel findings on the potential of herbivore introduction as an indirect biomanipulation tool for halting the regime shift of shallow lakes from clear to turbid after the restoration of submerged macrophytes. Graphical abstract: Image 1 Highlights: Lake management focus few on clear-water state maintenance. We studied the potential of herbivores for regime shift prevention of clear-water. Herbivores reduced endogenous nutrient accumulation rather than underwater light. Herbivores enhanced submerged macrophyte inhibition ratio of phytoplankton.